1992
DOI: 10.1002/cae.6180010110
|View full text |Cite
|
Sign up to set email alerts
|

Interactive video: Innovative episodes for enhancing education

Abstract: This article provides information about the actual and potential uses of interactive videõ n instruction i.n an effort to motivate educators to consider using this technology to tmprov.e teachmg. The authors (I ) describe the continuing evolution of computer-based educational tools;(2) examine instances when an interactive videodisc provides viable instructional solutions to otherwise very difficult or impossible tasks; (3) discuss several models for delivering instruction to accommodate different learning sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Here, too, the findings have been mixed. Bailey and Thornton (1992) studied the impact of an interactive video lesson on student achievement and found no significant relationship. And Shaw, Arnason, and Belardo (1993) found no effect of interactivity on knowledge gain.…”
Section: Conceptual Framework and Research Questionsmentioning
confidence: 99%
“…Here, too, the findings have been mixed. Bailey and Thornton (1992) studied the impact of an interactive video lesson on student achievement and found no significant relationship. And Shaw, Arnason, and Belardo (1993) found no effect of interactivity on knowledge gain.…”
Section: Conceptual Framework and Research Questionsmentioning
confidence: 99%
“…Interactive multimedia can be used to support education and training, to serve as a reference tool and to provide dynamic presentations [1] [2]. Educational research showed that if information is conveyed to the students in a combination of text, color, graphics, animation, sound, moving pictures, and a degree of interactivity, the interactive multimedia approach may result in a significant increase in retention, improvement in the learning rate and active learning process [3]- [5]. According to Stoney and Oliver's report, "The use of interactive multimedia can foster and develop cognitive engagement through its ability to attract and hold students' attention and focus."…”
Section: Relation Of Petl To Previous Researchmentioning
confidence: 99%
“…Fortunately, this uncertainty in understanding the role of computers and software tools in engineering education has coincided with rapid growth in the area of multimedia presentations [3]. Interactive video applications integrate the visual power of video, interactivity of software, and an ability to structure educational lessons that include tutorials, quizzes, and maintenance of scores for the instructor's use.…”
Section: Introductionmentioning
confidence: 99%